Ultrasonographic Assessment of Soft Tissues in Patients With Acromegaly - Mustafa KOÇAK,; Nadim CİVAN,; Murat KARKUCAK,; Erhan ÇAPKIN,; Melek GARİPOĞLU,; İpek CAN,; Adem KARACA,; Mustafa TAŞDELEN,; Ahmet AYAR, (Archives of Rheumatology, 2015)
Objectives: This study aims to investigate ultrasound examination findings of cartilage, tendon and nerve structures in patients with acromegaly and assess whether imaging findings have any association with the clinical and laboratory features of the patients. Patients and methods: The study included 38 diagnosed acromegaly patients (18 males, 20 females; mean age 45.6±10.4 years; range 28 to 63 years) and 21 control subjects (8 males, 13 females; mean age; 43.1±7.4 years; range 29 to 58 years) similar for age, sex and body mass index. Patients’ clinical characteristics and laboratory parameters were recorded. The cross sectional area of median nerve, flexor pollicis longus and Achilles tendon, and humeral cartilage thickness were bilaterally assessed by ultrasound. Results: Arthralgia was present in 13 patients (34.9%) and 11 (28.9%) had paresthesia in the hands. Thickness of humeral cartilage and the cross sectional area of median nerve, flexor pollicis longus tendon and Achilles tendon was significantly higher in acromegaly patients compared with controls (p<0.001). While measurements performed with ultrasound were correlated among themselves, no significant correlation was present between ultrasound measurements and growth hormone and insulin-like growth factor-1. When acromegaly patients were analyzed as active (n=22) and inactive (n=16), no significant difference was determined in the parameters with the exception of median nerve measurements. Conclusion: Ultrasound examination revealed significantly different cartilage, tendon and nerve parameters in acromegaly patients compared to the control group. Median nerve cross sectional area was significantly greater in active patients compared to inactive patients.